Multimodal Project-Based Learning in listening and speaking activities: Building environmental care? - Lulut Widyaningrum; Daviq Rizal; Agus Prayogo (EduLite: Journal of English Education, Literature and Culture, 2022)
This Participatory Action Research (PAR) aims to describe how the enactment of Multimodal Project-Based Learning of Green Listening is in Extensive Listening and Speaking class of English Language Education Department, UIN Walisongo, how Multimodal Project-Based Learning of Green Listening and Speaking facilitates students’ listening and speaking skills, and how Multimodal Project-Based Learning of Green Listening and Speaking facilitates environmental care within students. Twenty-four students and one teacher were recruited purposively as participants. Findings showed that enacting multimodal project-based learning aiming to facilitate language skills and build environmental awareness is a complex and staged process requiring the participation of researchers, teachers, and students. Further research needs to look into the perspectives of teachers while designing a multimodal language learning project. In addition, the investigation of the instructional design in conjunction with the project must be thoroughly scrutinized.